Site-specific N-application in small-scale arable farming in Germany—Evaluation of trade-offs and synergies of ecological and economic parameters based on a case study - Rolf Weber; Johannes Munz; Jürgen Braun; Markus Frank (Discover Sustainability)
Abstract The potential of site-specific fertilization holds great promise for more efficient fertilizer use, which can make crop production more sustainable. The challenges for farmers to produce food more sustainably are increasing. With site-specific fertilization, the heterogeneity of the soil in the field can be taken into account when applying fertilizer. In this paper, the use of site-specific fertilization is investigated in terms of economic and environmental trade-offs and synergies based on on-farm trials. In total, on-farm-research trials were evaluated on three farms over a period of three years of data collection. The results are compared with uniform fertilization. The effects of site-specific fertilization are calculated economically using cost–benefit analysis in combination with a sensitivity analysis, while the ecological evaluation is carried out using the carbon footprint method. The results show that the yield could be increased by an average of 5.6% with site-specific fertilization. This also has environmental benefits, as more yield is achieved with the same input, which reduces emissions per tonne of grain by 5.1%. Economically, however, there are large uncertainties in balancing the additional costs with the benefits of site-specific fertilization. Taking into account the results of the sensitivity analysis, the additional costs can only be covered in 11 out of 30 cases. The results of the case study show that the use of site-specific fertilization can increase the environmental sustainability of agriculture, regardless of the size of the farm. From an economic point of view, the results show that the size of the farm is decisive for the profitability of site-specific fertilization. The smaller the farm size, the higher the costs per unit associated with the technology.